Diffusimetry Renounces Graham’s Law, Achieves Diffusive Convection, Concentration Gradient Induced Diffusion, Heat and Mass Transfer - Alim, Mohammad Abdul; Mahamud, Sultan; Khair, Abul; Bahadur, Newas Mohammad; Dey, Nilay Kumar; Ahmed, Syekat; Harun-Ur-Rashid, Mohammad (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
Absolute diffusion rates of KMnO4 in vertical and flattened diffusimeters show the concentration gradient force as being stronger than the gravitational force. Hot water molecules move downward on self-diffusion against buoyancy. Diffusive convection (DC) in warm water and double-diffusive convection (DDC) in warm, saline water take place inside the diffusimeter with DDC transferring more heat than DC. In the diffusing medium the original reagents change or retain their compositions to give the diffusate molecules to diffuse. In water, the change is mostly hydration. The syngener BaCl2.2H2O separately with congeners 3CdSO4.8H2O, ZnSO4.7H2O, and ZnSO4.H2O presents two distinct pairs of overlapping concentration versus rate curves, first for having very close MWs of BaCl2 and CdSO4 and second for having ZnSO4.H2O as the common congener for both the zinc sulfates. Chlorides of Li, Na, and K diffusing at hindered rates in glucose solution show the least rate for LiCl inevitably on grounds of low mass and high Li+ hydration radius. Diffusion blocking occurs at higher glucose concentration. Diffusion of 0.6M AgNO3-0.6M NH4Cl standardizes this diffusimeter. Mass transfer of HCl, H2SO4, and H2C2O4 show oxalic acid diffusing as hydrate and 88 percentage transfer of sulfuric acid in 5 minutes. The Superdiffusive Anti Graham’s Law, Vd ∝√M , is further consolidated by Ca (NO3)2-M2CO3(M = Na, K, NH4+) and Ca (NO3)2-Na2HPO4 diffusions. Odd and even diffusions are illustrated by AgNO3-NH4Cl and AgNO3-BaCl2 diffusions.